Analisis Faktor Penyebab SiLPA dan SILPA Pada Badan Pengelola Keuangan dan Aset Daerah Kabupaten Musi Banyuasin - Ahmad Irfansyah (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2020)
This study aims to determine the factors that cause the remainder of the budget calculation (SiLPA) and the remainder over budget financing (SILPA) in the Financial Management and Assets Board of the District of Musi Banyuasin in period of 2016 to 2018.. This study uses a qualitative method. Data collection techniques are carried out through field studies by conducting documentation and interviews, literature studies from literature references that support this research. Data analysis techniques start from qualitative data in the form of Reports on the Realization of Regional Income and Expenditure Budgets and Reports on Changes in Budget Balances. The Results of study indicate that the high and low levels of SiLPA that occurred in BPKAD in the District of Musi Banyuasin in the period 2016 to 2018 caused by exceeding income, remaining expenses or other consequences. While SILPA is caused by an increase in regional income, the absorption of the regional budget that is not optimal, the low absorption of unexpected expenditure, the high level of financing receipts but the low cost of financing which means that there are funds that are not utilized optimally, the quantity of human resources in lacking so that the planned target achievement is not optimal.